Crystallization kinetics in phosphate sodium-based glass studied by DSC technique - Reynoso, VCS; Yukimitu, K.; Nagami, T.; Carvalho, C. L.; Moraes, João Carlos Silos [UNESP]; Araujo, E. B. (Elsevier B.V., 2003)
In this work, differential scanning calorimetry (DSC) was used to study the mechanism of crystallization of 5OP(2)O(5-)27.8Na(2)O-16ZnO-6.2Al(2)O(3) glass. DSC measurements were performed on bulk and powdered glasses with different particle size. The curve for bulk glass shows one crystallization peak while powdered glasses presented two distinct crystallization peaks. Based on DSC studies, the activation energies obtained were 336 +/- 6 and 213 +/- 3 U mol(-1), associated with first and second crystallization peaks, respectively. Analyzing the DSC parameters as a function of particle size, the Avrami n parameter suggests that the peak at low temperature may be associated with surface crystallization while the peak at high temperature is associated with bulk crystallization. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: differential scanning calorimetry; X-ray diffraction; glasses